2012
DOI: 10.1186/1423-0127-19-10
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalization of the exitatory amino-acid transporters (EAATs) in human astrocytoma and non-astrocytoma cancer cells: effect of the cell confluence

Abstract: BackgroundAstrocytomas are cancers of the brain in which high levels of extracellular glutamate plays a critical role in tumor growth and resistance to conventional treatments. This is due for part to a decrease in the activity of the glutamate transporters, i.e. the Excitatory Amino Acid Transporters or EAATs, in relation to their nuclear mislocalization in astrocytoma cells. Although non-astrocytoma cancers express EAATs, the localization of EAATs and the handling of L-glutamate in that case have not been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Gene expression analyses identified a high expression of SOX2 in high-grade glioma cultures [14] except glioma cultures of mesenchymal origin. Some reports indicate that during tumor development glioma cells may lose or translocate some of their surface transporters [15, 16], and our data demonstrating strong ASP + uptake in cultured and implanted GL261 glioma cells during the first two weeks after implantation in mouse brain and significant reduction of ASP + uptake in older tumors support these findings. Thus OCT family transporters are initially overexpressed in many gliomas and ASP + can be used as a fast and effective glioma marker.…”
Section: Asp+ Staining Reveals the Internal Tumor Structuresupporting
confidence: 88%
“…Gene expression analyses identified a high expression of SOX2 in high-grade glioma cultures [14] except glioma cultures of mesenchymal origin. Some reports indicate that during tumor development glioma cells may lose or translocate some of their surface transporters [15, 16], and our data demonstrating strong ASP + uptake in cultured and implanted GL261 glioma cells during the first two weeks after implantation in mouse brain and significant reduction of ASP + uptake in older tumors support these findings. Thus OCT family transporters are initially overexpressed in many gliomas and ASP + can be used as a fast and effective glioma marker.…”
Section: Asp+ Staining Reveals the Internal Tumor Structuresupporting
confidence: 88%
“…This suggests that the mislocalized transporter remains active in the nucleus, pumping fluorescent substrate to the inside of the nucleus of migrating glioma cells. The functionality of transporters has not been studied for other transporters reportedly also mislocalized in gliomas [23]. The only study describing functional mislocalization to the nucleus is the case of CXCR4 mislocalization in prostate-cancer cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous reports have emerged that some important transporters, receptors and channels, normally presented in the plasma membrane can be mislocalized in gliomas and, generally, in cancer cells, to the nuclei. It was shown that glutamate transporters became mislocalized to the nucleus in glioma cells that depends upon cellular confluence or the amount of cells in the tumor (tumor size) [25, 23]. Also, potassium inward-rectifying channels Kir 4.1 and Kir 2.3 in glioma cells are found almost exclusively in either the cell nucleus or endoplasmic reticulum/Golgi apparatus (Kir 3.1) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly and contrarily to what we found with another mycotoxin, ochratoxin A [148], such inhibition is associated to a massive increase in the membrane expression of EAAT1/2 through an unidentified mechanism. Inhibition induced by DON of the glutamate uptake by astrocytes may have major consequences since this activity prevents neuronal damage caused by high excitotoxic extracellular glutamate concentrations [149] and that perturbation of glutamate clearance by astrocytes could also contribute to brain tumor progression [150], pain hypersensitivity [151] and to alterations in learning and memory consolidation [152]. Although very interesting, these in vitro data showing the perturbation of glial cells by DON now need to be confirmed by in vivo studies.…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%